A VERY BRASILERIO PORTUGUESE: AN INTERDISCIPLINARY PERSPECTIVE TO THE ASSESSMENT OF SPEECH METATHESIS IN ADDITIONAL LANGUAGE PORTUGUESE TEACHING CONTEXTS - Oliveira, Diego Fernando de [UNESP] (Univ Estado Mato Grosso, 2023)
This paper aims to revisit the literature on metathesis and to propose a translinguistic and pluricentric perspective to its assessment in teaching-learning contexts of Portuguese as an additional language. Methodologically, this work is outlined as a literature review. Based on the analysis of nine scientific productions available in online databases that address metathesis, this paper points out the tendency to interpret metathesis as a natural phenomenon of the linguistic development process, motivated by the phonological structure of the sequences and the linguistic knowledge of the speaker. Finally, it proposes a reflection on the assessment of metathesis in teaching-learning contexts of Portuguese as an additional language.
Keywords: metathesis; Portuguese as an additional language; translinguism; pluricentrism